REDUCING LOST TIME DUE TO SHIFT CHANGES FROM 7.00 HOURS TO 4.60 HOURS FOR THE PERIOD OF FEBRUARY – JULY 2024 TO INCREASE PRODUCTION ACHIEVEMENT AND OVERBURDEN PRODUCTIVITY OF PC2000 AT PT ANTAREJA MAHADA MAKMUR JOBSITE MIFA BERSAUDARA - Yuwono, F. Joko; Hutapea, Selly M.; Suksmapranata, Ifani (International Journal of Social Service and Research, 2024)
The mining industry is facing the dual challenge of meeting the demand for raw materials while minimizing environmental impact and ensuring sustainable practices. As urbanization accelerates, the industry is increasingly adopting advanced technologies and methodologies to enhance efficiency and reduce waste. The purpose of the research is to analyze and implement strategies that minimize the downtime associated with shift changes in order to enhance overall production efficiency and productivity of the PC2000 machinery at the specified jobsite. The study aims to quantify the impact of reducing shift change time on production outcomes and overburden productivity, ultimately contributing to improved operational performance within the defined timeframe. The research contributes to the field of operational efficiency by providing empirical insights into the relationship between reduced shift change times and enhanced production performance in heavy machinery operations. The findings may serve as a valuable reference for similar industries aiming to optimize shift management and improve overall operational productivity, thus contributing to best practices in resource management and efficiency enhancement. Furthermore, comparative studies with other mining operations that have successfully implemented similar changes could provide a broader perspective on best practices and innovative strategies, contributing to the overall advancement of the mining industry.